(untitled) (Zaporizhzhia Historical Review, 2021)
This article focuses attention on the differences in methodologies of Soviet and world historians. The author arrives at the conclusion that some Soviet historiansí contributions to the world heritage are comparable to the best achievements in this sphere. They are connected first of all with the names of I.D.Kovalchenko (introduction into history research of the newest scientific methods), M.A.Barg (approbation of various structural methods), A.J.Gurevich (developing of methods of historical and cultural anthropology).